DFT Study of Leuco-Indigo and Indigo as Active Material in Dye-Sensitized Solar Cell - Maahury, Mirella Fonda; Male, Yusthinus Thobias; Martoprawiro, Muhamad Abdulkadir (Molekul, 2020)
Computational study of natural indigo has been carried out to get the optimized structure and electronic properties of two indigo at different pH. It has been found that indigo has the potential to be applied as active material in the dye-sensitized solar cell. Computational calculations are performed using Density Functional Theory (DFT) with B3LYP functional and 6-31G(d,p) for ground state geometry optimization and Time Dependent-Density Functional Theory (TD-DFT) for excited states single point calculation. All calculations are carried out in the gas phase. Geometry optimization results show that Indigo has a planar structure, whereas leuco-indigo structure is not planar. Leuco-indigo absorption wavelength is shorter than indigo. The density of HOMO and LUMO is spreading throughout the molecule. The density of electrons at LUMO extends to the anchoring group. Based on excitation energy, absorption wavelength, excitation composition, and HOMO-LUMO density, it can be concluded that indigo has the potential to be applied in dye-sensitized solar cell (DSSC)